2018
DOI: 10.5194/acp-18-445-2018
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of atmospheric gases and aerosols with the monsoon dynamics over the Sudano-Guinean region during AMMA

Abstract: Abstract. Carbon monoxide, CO, and fine atmospheric particulate matter, PM 2.5 , are analyzed over the Guinean Gulf coastal region using the WRF-CHIMERE modeling system and observations during the beginning of the monsoon 2006 (from May to July), corresponding to the Africa Multidisciplinary Monsoon Analysis (AMMA) campaign period.Along the Guinean Gulf coast, the contribution of longrange pollution transport to CO or PM 2.5 concentrations is important. The contribution of desert dust PM 2.5 concentration decr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…The analysis shows that (a) the large pollution plumes observed at the coast up to 1.5 km (features A and B) are essentially related to emissions in the Lomé area from both 1 and 2 July, with a moderate contribution from Accra and Cotonou, (b) the elevated plume over the northern part of the Gulf of Guinea (feature C) is related to emissions from Accra exclusively from the day before the ATR 42 flight (i.e. 1 July) and these clearly dominate the composition of the tracer plume in the region covered by the flight track on 2 July, (c) given the general direction of the monsoon flow, Lagos emissions (taken to be 13 times that of Cotonou) do not appear to have affected the atmospheric composition west of Cotonou, where our airborne observations were gathered, as also shown by Deroubaix et al (2018) in post-monsoon onset conditions, and (d) the tracer plumes do not extend very far over the ocean during the short period under scrutiny, mostly because they are transported north-ward within the marine ABL and westward above it so that their extent is controlled by the equatorward component in the mostly easterly flow as modulated by synoptic-scale disturbances (Knippertz et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The analysis shows that (a) the large pollution plumes observed at the coast up to 1.5 km (features A and B) are essentially related to emissions in the Lomé area from both 1 and 2 July, with a moderate contribution from Accra and Cotonou, (b) the elevated plume over the northern part of the Gulf of Guinea (feature C) is related to emissions from Accra exclusively from the day before the ATR 42 flight (i.e. 1 July) and these clearly dominate the composition of the tracer plume in the region covered by the flight track on 2 July, (c) given the general direction of the monsoon flow, Lagos emissions (taken to be 13 times that of Cotonou) do not appear to have affected the atmospheric composition west of Cotonou, where our airborne observations were gathered, as also shown by Deroubaix et al (2018) in post-monsoon onset conditions, and (d) the tracer plumes do not extend very far over the ocean during the short period under scrutiny, mostly because they are transported north-ward within the marine ABL and westward above it so that their extent is controlled by the equatorward component in the mostly easterly flow as modulated by synoptic-scale disturbances (Knippertz et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…For the two horizontal resolutions, the same physical parameterizations are used and are those described in Deroubaix et al (2018). The ABL scheme is the one proposed by Yonsei University , the microphysics is calculated using the Single Moment-6 class scheme (Hong and Lim, 2006), the radiation scheme is RRTMG (Mlawer et al, 1997), the cumulus parameterization is the Grell-Dévényi scheme, and the surface fluxes are calculated using the Noah scheme (Ek et al, 2003). The 10 km WRF simulation uses National Centers for Environmental Prediction (NCEP) Final global analyses as initial and boundary conditions.…”
Section: Wrf and Chimere Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…DACCIWA studies confirmed the importance of an import of aerosol from fires in Central Africa in addition to local pollution sources Haslett et al, 2019a). The strong monsoon flow during the LDS causes a fast spread of pollutants from the main sources in coastal cities inland (Deroubaix et al, 2019). Given the overall high concentration of aerosol particles and predominantly stratiform clouds, relatively little susceptibility of cloud microphysics to aerosol effects was found (Deetz et al, 2018b;Taylor et al, 2019).…”
Section: Introductionmentioning
confidence: 78%
“…Submicron aerosol chemical composition was measured using Aerodyne compact time-of-flight aerosol mass spectrometers (AMSs) (Drewnick et al, 2005;Canagaratna et al, 2007), mounted on board all three aircraft. The instrument samples submicron particles from ambient air through an aerodynamic lens, which focuses the particles in the vacuum chamber into a narrow beam.…”
Section: Airborne Observationsmentioning
confidence: 99%